Oxidative Chemical Vapor Deposition of Conducting Polymer Films on Nanostructured Surfaces for Piezoresistive Sensor Applications. (28th December 2020) - Muralter, Fabian; Coclite, Anna Maria; Lau, Kenneth K.S.
Abstract: In this study, a novel, fully polymeric setup for piezoresistive sensing is prepared and tested. Monolayers of polystyrene (PS) nanospheres are assembled on flexible polyethylene naphthalate substrates. Subsequently, thin layers (≈50–100 nm) of poly(3, 4‐ethylenedioxythiophene) (PEDOT) are deposited conformally around the spheres by oxidative chemical vapor deposition (oCVD). Voltage−current characteristics and direct resistance measurements are performed to test the electrical properties of the samples in their unstrained state and their piezoresistive response during bending. Substrate deposition temperature ( T sub ) and film thickness ( t PEDOT ) are used as parameters to alter properties of the PEDOT thin films; increased T sub and t PEDOT lead to samples exhibiting lower intrinsic resistance. The electrical conductivity of the samples is estimated to range as high as tens of S cm −1 . Dopant exchange of the oCVD‐PEDOT layer (intrinsically, chlorine‐doped) is performed by putting the samples in 0.5 m sulfuric acid, which decreases their resistance by ≈1/3. Regarding the piezoresistive properties of the devices, acid treatment, higher T sub and t PEDOT (thus, lower intrinsic resistance) yield samples with increased response. As a result, gauge factors as high as 11.4 are achieved. Due to their flexibility and low‐cost, the proposed structures can be readily employed as skin‐inspired or wearable electronic devices. Abstract : A novel, fully polymeric setup for piezoresistive sensing is developed and prepared by vapor depositing a layer of poly(3, 4‐ethylenedioxythiophene) (PEDOT) conformally around polystyrene (PS) nanospheres on a flexible substrate. Via two nickel top‐contacts, the resistance and piezoresistive response (resistance change upon straining) of the samples is investigated as a function of processing parameters. Gauge factors as high as 11.4 are achieved.